Daylength, Temperature and Solar Radiation Effects on the Phenology and Yield Formation of Spring Durum Wheat. (30th July 2015) - Villegas, D.; Alfaro, C.; Ammar, K.; Cátedra, M. M.; Crossa, J.; García del Moral, L. F.; Royo, C.
Abstract: Future food security will depend on crop adaptation to changing environments. We studied the limitations imposed by daylength, temperature and solar radiation on wheat yield in eight field experiments conducted at contrasting northern latitudes and involving 42 adapted spring durum wheat genotypes of divergent phenology, and reduced or without photoperiod sensitivity. Air temperatures averaged from sowing to anthesis (SA) increased from northern to southern sites, while daylength and minimum temperatures from anthesis to maturity (grain filling, GF) followed the opposite trend, due to differences in the latitude of sites. The site effect explained 96 % of the variation in the number of days SA, which was much smaller in southern sites. Average minimum daily temperatures above 6.9 °C before anthesis and below 10.8 °C during GF accompanied by photoperiods during GF of less than 14.2 h resulted in less than 14 000 kernels m −2, which was the threshold below which kernel number limited yield. Radiation during GF lower than 1.8 kJ kernel −1 day −1 limited kernel weight, which was then a constraint to the achievement of yield potential.